1997
DOI: 10.1128/iai.65.4.1550-1556.1997
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal accessory regulator (sar) in conjunction with agr contributes to Staphylococcus aureus virulence in endophthalmitis

Abstract: Previous studies showed that an agr mutant strain of Staphylococcus aureus was partially attenuated in virulence compared to a parental strain in experimental endophthalmitis. The purpose of this study was to determine whether the sar locus, either alone or through interactions with agr, contributes to the regulation of virulence in S. aureus endophthalmitis. Experimental endophthalmitis was established by the midvitreous injection of approximately 30 CFU of S. aureus RN6390 or the isogenic attenuated strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 32 publications
3
76
0
Order By: Relevance
“…An analogous phenomenon such as enhanced repression of exotoxin-encoding genes in double mutants of regulatory genes in S. aureus is not uncommon. For example, sar and agr double mutants are less virulent compared with the agr single mutant (Booth et al, 1997). Differences in the transcript levels of regulatory genes (agr, sarA, sigB, and saeR/S) have been reported between COL and Newman strains that correlate well with the expression of virulence-associated genes (Rogasch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…An analogous phenomenon such as enhanced repression of exotoxin-encoding genes in double mutants of regulatory genes in S. aureus is not uncommon. For example, sar and agr double mutants are less virulent compared with the agr single mutant (Booth et al, 1997). Differences in the transcript levels of regulatory genes (agr, sarA, sigB, and saeR/S) have been reported between COL and Newman strains that correlate well with the expression of virulence-associated genes (Rogasch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further, sarA activates the agr regulatory system that is linked to several virulence factors (Blevins et al, 1999(Blevins et al, , 2002Chan and Foster, 1998). The sarA and agr loci have been implicated in the virulence of a number of disease models (Booth et al, 1997;Cheung and Ying, 1994;Kielian et al, 2001). sarA is essential for biofilm formation in S. aureus (Beenken et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ocular infection models have been developed in rabbits. Experimental endophthalmitis studies showed that an agr mutant causes less severe clinical and histological signs than the wild-type strain [90], strongly suggesting that toxin production contributes to virulence. This was further confirmed in the same model of endophthalmitis, where agr, but not sarA alone, influenced virulence.…”
Section: Impact Of Regulatory Systems In Vivomentioning
confidence: 99%
“…This was further confirmed in the same model of endophthalmitis, where agr, but not sarA alone, influenced virulence. However, the double mutant had a greater effect [91]. In a rat endophthalmitis model, Giese et al [92] reported that an agr/sarA double mutant strain induced less inflammatory cell recruitment than the wild-type strain, implying that pore-forming toxins may play a major role.…”
Section: Impact Of Regulatory Systems In Vivomentioning
confidence: 99%